Structural Mass Spectrometry of the αβ-Tubulin Dimer Supports a Revised Model of Microtubule Assembly() - Bennett, Melissa J. (2009)
The molecular basis of microtubule lattice instability derives from the hydrolysis of GTP to GDP in the lattice-bound state of αβ-tubulin. While this has been appreciated for many years, there is ongoing debate over the molecular basis of this instability and the possible role of altered nucleotide occupancy in the induction of a conformational change in tubulin. The debate has organized around seemingly contradictory models. The allosteric model invokes nucleotide-dependent states of curvature in the free tubulin dimer, such that hydrolysis leads to pronounced bending and thus disruption of the lattice. The more recent lattice model describes a predominant role for the lattice in straightening free dimers that are curved regardless of their nucleotide state. In this model, lattice-bound GTP-tubulin provides the necessary force to straighten an incoming dimer. Interestingly, there is evidence for both models. The enduring nature of this debate stems from a lack of high-resolution data on the free dimer. In this study, we have prepared αβ-tubulin samples at high dilution and characterized the nature of nucleotide-induced conformational stability using bottom-up hydrogen/deuterium exchange mass spectrometry (H/DX-MS) coupled with isothermal urea denaturation experiments. These experiments were accompanied by molecular dynamics simulations of the free dimer. We demonstrate an intermediate state unique to GDP-tubulin, suggestive of the curved colchicine-stabilized structure at the intradimer interface but show that intradimer flexibility is an important property of the free dimer regardless of nucleotide occupancy. Our results indicate that the assembly properties of the free dimer may be better described on the basis of this flexibility. A blended model of assembly emerges in which free-dimer allosteric effects retain importance, in an assembly process dominated by lattice-induced effects.